Qualidade, maturação e vida útil pós-colheita de duas cultivares de videiras produzidas sob três porta-enxertos no município de Mossoró/RN - Nascimento, Paula Lidiane de Oliveira Fernandes do (2016)
The viticulture has been expanding its cultivation in many regions of the country. Considering his success in the Northeast, in the Vale do São Francisco, research must be done to stimulate the development of this culture in new regions. The objective of this research was to evaluate the development of two grapevine cultivars produced in three rootstocks in Mossoró/RN, assessing maturity, quality and postharvest life of fruit. The experiment was conducted at the Experimental Farm Rafael Fernandesfrom 2013 to 2015. We used the design of randomized blocks with split plots for the three experiments. The first experiment evaluated the quality of the fruit in four crop cycles, with the rootstock (IAC 766, IAC 572 and IAC 313) in the plots and crop cycles subplots. In the second experiment, the treatments were three rootstocks (IAC 766, IAC 572 and IAC 313) and four maturity stages (14, 19, 24 and 28 days after the start of the color change of the berry) with five repetitions for Isabel Precoce. In the third experiment, we evaluated the shelflife of vine cultivars stored under refrigeration (4 ± 2 ° C and 95 ± 5% RH), where plots were assigned to rootstocks (IAC 766, IAC 572 and IAC 313) and time storage were assigned to the subplots. In third experiment for cultivar Isabel Precoce, storage times were 10, 20, 30, 40 and 50 days after harvest; to cultivar Itália Melhorada, were 8, 16, 24 and 32 days of storage after harvest. The characteristics evaluated for the three experiments were: mass of the bunch, number and berry mass, peel mass, berry length, berry diameter, color Berry (L, A * and B *), firmness (N) mass loss, wilting index stalk and injuries, soluble solids (SS), titratable acidity (TA), pH, SS/AT ratio, total and reducing sugars, anthocyanins, flavonoids, phenolic compounds and antioxidant activity. For the cycles of Isabel cultivar, the bunch weight and the number of berries were higher in the 3rd and 4th cycles; but the physical and chemical characteristics, as soluble solids, SS/AT ratio and sugar, were higher in the 1st cycle; as the bioactive compounds, phenolic and antioxidant activity was higher in the 4th harvest (first semester 2015). For cultivar Itália Melhorada, the 1st cycle gave higher soluble solids and SS/AT ratio, and the rootstock 766 shown superiority; in the second cycle, the mass of the bunch and number of berry was greater, and the rootstock 572 most massive result of the bunch. The ideal point of Isabel Precoce grape harvest is 28 days after the beginning of the maturation. The rootstock had a significant effect only for the SS/AT ratio, and highlight the IAC 766; for bioactive compounds, there was an increase with the maturation only for the phenolic content in the peel and pulp and anthocyanins, the other compounds did not vary throughout the maturation. Regarding storage the cultivar Isabel Precoce had a Shelflife relatively long, 50 days of storage at 4 ° C ± ± 2ºC and 90 ± 5% RH; the cultivar Itália Melhorada had a limited shelf life to 24 days of storage (4 ° C ± 2ºC and 90 ± 5% RH). As for the rootstocks used, the 766 and 572 had higher soluble sugar content for Isabel Precoce cultivar and higher soluble solids and total sugars to cultivar Itália Melhorada